Effectiveness of an O-Alkyl Hydroxamate in Dogs with Naturally Acquired Canine Leishmaniosis: An Exploratory Clinical Trial - Victoriano Corpas-López; Victoriano Díaz-Sáez; Francisco Morillas-Márquez; Francisco Franco-Montalbán; Mónica Díaz-Gavilán; Julián López-Viota; Margarita López-Viota; José Antonio Gómez-Vidal; Joaquina Martín-Sánchez (Animals, 2022)
Canine leishmaniosis is a challenge in veterinary medicine and no drug to date has achieved parasite clearance in dogs. Histone deacetylase inhibitors are a drug class widely used in cancer chemotherapy. We have successfully used O-alkyl hydroxamates (vorinostat derivatives) in the treatment of a laboratory model of visceral leishmaniasis without showing toxicity. In order to test the effectiveness of a particular compound, MTC-305, a parallel-group, randomized, single-centre, exploratory study was designed in naturally infected dogs. In this clinical trial, 18 dogs were allocated into 3 groups and were treated with either meglumine antimoniate (104 mg SbV/kg), MTC-305 (3.75 mg/kg) or a combination of both using a lower MTC-305 dose (1.5 mg/kg) through a subcutaneous route for 2 treatment courses of 30 days, separated by a 30-day rest period. After treatment, a follow-up time of 4 months was established. Parasite burden in bone marrow, lymph node and peripheral blood were quantified through qPCR. Antibody titres were determined through an immunofluorescence antibody test, and cytokine expression values were calculated through RT-qPCR. Treatment safety was evaluated through the assessment of haematological and biochemical parameters in blood, weight, and gastrointestinal alterations. Assessment was carried out before, between and after treatment series. Treatment with MTC-305 was effective at reducing parasite burdens and improving the animals’ clinical picture. Dogs treated with this compound did not present significant toxicity signs. These results were superior to those obtained using the reference drug, meglumine antimoniate, in monotherapy. These results would support a broader clinical trial, optimised dosage, and an expanded follow-up stage to confirm the efficacy of this drug.